داعیانِ دین کے لیے فہمِ بلاغتِ قرآنی کی علمی و دعوتی اہمیت: The Scholarly and Missionary Significance of Understanding Qur’anic Eloquence for Islamic Preachers - Dr. Faryal Umbreen; Muhammad Jafir (Al-Amīr Research Journal for Islamic Studies, 2025)
This article explores the scholarly and missionary importance of understanding the Qur’anic eloquence (balāgha) for Islamic preachers (duʿāt). The Qur’an is not only a divine book of guidance but also a linguistic miracle whose rhetorical power has captivated audiences for centuries. For preachers, mastering its eloquence enables more impactful, persuasive, and spiritually resonant communication. In a time when conveying religious truths requires both intellectual rigor and emotional appeal, the Qur’anic use of storytelling, metaphors, parables, and contrasting themes offers a deeply effective model. This paper argues that comprehension of Qur’anic balāgha strengthens a preacher’s message, allowing it to reach hearts and minds with clarity and power. Therefore, understanding the eloquence of the Qur’an is a vital asset for any contemporary Islamic missionary. Keywords: Qur’anic Eloquence, Balāgha, Islamic Preaching, Da‘wah, Rhetoric, Religious Communication, Qur’anic Narrative, Islamic Missionary Work